A gene family in Drosophila melanogaster coding for trypsin-like enzymes. - Davis, C.A.; Riddell, D.C.; Higgins, M.J.; Holden, J.J.; White, B.N. (Nucleic Acids Research, 1985)
We have isolated a clustered gene family in D. melanogaster that codes for trypsin-like enzymes. The gene family has been localized to 47D-F by in situ hybridization to polytene chromosomes. The four genes in the family are transcribed in alternating orientations, and code for 1000 nt mRNAs. Transcripts are present at all stages of the life cycle. In situ hybridization to mRNA in tissue sections of third instar larvae showed that transcripts were restricted to the mid-gut. One gene was sequenced. The translated amino acid sequence of the proposed active enzyme is 42% homologous to bovine trypsin. Regions of functional importance are more strongly conserved. These include the active site residues asp102, his57, ser195, and the residue asp189 which is reputed to bind the basic residue at the substrate cleavage site. The activation peptide is not homologous to that of most vertebrate trypsins, suggesting a modified activation mechanism. The sequence further strengthens the hypothesis that the chymotrypsin cleavage specificity developed separately in the vertebrates and invertebrates.